Operative hysteroscopy intravascular absorption syndrome: The gynecological transurethral resection syndrome - Rajeev Chauhan; Venkat Ganesan; Ankur Luthra (Journal of Obstetric Anaesthesia and Critical Care, 2018)
Hysteroscopy is becoming fairly common in most centers these days, both as a diagnostic and therapeutic tool especially for short day-care procedures, reducing unnecessary hospital admissions and overuse of resources. However, these procedures are not without complications, and some could be delayed and potentially fatal if a high index of suspicion is not maintained. One such rare yet one with a high mortality among urological patients is the transurethral resection syndrome on which there is a cornucopia of literature in the form of articles and chapters. There are very few highlighting a similar syndrome of sorts called the operative hysteroscopy intravascular absorption syndrome. Here, we describe one such case, and in brief, the anesthetic management options for hysteroscopic procedures to prevent such a complication.